DETERMINATION OF THE INFLUENCE OF SALICYLIC ACID ON THE GERMINATION AND DEVELOPMENT OF BARLEY PLANTS (HORDEUM VULGARE L.) - Pleșca Vlad George*,; Memete Adriana Ramona*; Vicaș Simona Ioana* (Natural Resources and Sustainable Development, 2025)
To evaluate the effect of concentrations and time of grain soaking, under the influence of salicylic acid (SA), on the germination and early growth of barley (Hordeum vulgare L.) plants, an experiment was carried out in a completely randomized design. Treatments consisted of four concentrations of SA (0, 25, 50 and 100 μM) with melting times every 24 h, up to 164 h (final monitoring time). Germination percentages, primary and secondary root growth, as well as stem and leaf growth, as well as chlorophyll and carotenoid content, were recorded. The results show that by sprinkling the seeds with 20 ml of SA solution, every 24 h, better and better results appear in the process of germination and development, compared to the control sample. The growth of the root, the length of the stem and the leaf was higher at the lowest concentration of SA (25 μM), but also in the case of the other concentrations they germinated and developed harmoniously, their germination not being inhibited. The same cannot be concluded, however, about the control sample, whose germination was very poor.